Evaluation of Nutritive Value of Some Citrus Pulp as Feedstuffs in Rabbit Diets - Ibrahim, M.R.; El-Banna, H.M.; Omara, I.I.; Suliman, Marwa A. (Pakistan Journal of Nutrition, 2011)
The present study was conducted to evaluate, determine nutrient digestibility and nutritive value of lemon pulp and orange pulp. The citrus by-products were replaced for yellow corn in the basal diet at 3 levels (20, 40 and 60%) for each by-product. A total number of 21 White New Zealand rabbits (NZW) at 8 weeks of age were individually weighed and randomly assigned individually into seven groups representing the seven experimental groups. Each group was divided into three replicates of one rabbit each. All animals were kept under the same management and hygienic conditions and were housed in metal battery cages supplied with separated feeders. Diets were offered ad-libitum and fresh water was available all times from automatic nipple drinkers. The experimental period lasted for 11 days. All rabbits were vaccinated against diseases and they were under veterinary control. The result showed that lemon and orange pulps are rich in CF, NDF, ADF, ADL, Hemi-cellulose and cellulose compared to yellow corn but CP and GE content for lemon and orange pulps are similarly equal compared to yellow corn. The content of vitamin C in lemon pulp and orange pulp was 0.068 g/100 g and 0.144 g/100 g compared with yellow corn 0.030 g/100 g, respectively. The anti-oxidant content of lemon pulp and orange pulp was 11.60 μl and 12.2 μl compared the yellow corn (8.29 μl) at 25 μl and 17.9 μl and 16.4 μl compared with 15.24 μl at 50 μl, respectively. The total saturated fatty acids content of lemon pulp and yellow corn was approximately equal but its content in orange pulp was higher than the yellow corn. Total unsaturated fatty acids content of lemon pulp and orange pulp were to be lower than that in yellow corn. There were insignificant differences in DM and Organic Matter (OM) digestibility among the experimental diets and control diet. The obtained results also that 40% substitution level of lemon pulp recorded the highest (p<0.05) value for CP digestibility (84.77%) compared others substitution levels of lemon pulp and control diet. The digestibility of Crude Fiber (CF) was recorded highest (p<0.05) value for 60% substitution level of orange pulp when compared to the control diet and other tested levels of lemon pulp and orange pulp. The Ether Extract (EE) digestibility was recorded the lowest (p<0.05) value with 60% substitution of lemon and orange when compared to the control diet and other substitution levels of lemon pulp. The diet containing 20% substitution level of orange pulp recorded highest (p<0.05) digestibility of NFE. While, the diet containing 60% substitution recorded lowest (p<0.05) value of DCP when compared to control diet and other substitution levels of lemon pulp. The different substitution levels of orange pulp showed insignificant differences when compared to the control diet. The Total Digestible Nutrients (TDN) and Digestible Energy (DE) recorded insignificant difference among control diet and 20, 40 and 60% substitution levels of lemon pulp. The diet containing 20% substitution level of orange pulp was higher in TDN and DE than the control diet. The diets containing 40 and 60% substitution levels for orange pulp recorded insignificant differences when compared to the control diet. Conclusively, replacing lemon pulp at levels of 20 and 40% and orange pulp at levels of 20 and 60% for yellow corn in rabbit diets achieved best nutrients digestibility and nutritive value.